2017
DOI: 10.1007/s00421-017-3716-8
|View full text |Cite
|
Sign up to set email alerts
|

Open-circuit respirometry: a historical review of portable gas analysis systems

Abstract: Scientists such as physiologists, engineers, and nutritionists have often sought to estimate human metabolic strain during daily activities and physical pursuits. The measurement of human metabolism can involve direct calorimetry as well as indirect calorimetry using both closed-circuit respirometry and open-circuit methods that can include diluted flow chambers and laboratory-based gas analysis systems. For field studies, methods involving questionnaires, pedometry, accelerometery, heart rate telemetry, and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 74 publications
0
26
0
Order By: Relevance
“…It seems clear that to reach a steady-state gaseous exchange (oxygen consumption and carbon dioxide production), a key requirement is to accurately measure substrate metabolism through indirect calorimetry. 50,51 In this context, previous studies have suggested that individuals with low cardiorespiratory fitness need longer time periods to reach the steadystate gaseous exchange. 52,53 Thus, the application of a 3-minute stage duration or less could not be enough to attain the steady-state gaseous exchange in specific populations.…”
Section: Time Interval For Data Selection and Analysismentioning
confidence: 99%
“…It seems clear that to reach a steady-state gaseous exchange (oxygen consumption and carbon dioxide production), a key requirement is to accurately measure substrate metabolism through indirect calorimetry. 50,51 In this context, previous studies have suggested that individuals with low cardiorespiratory fitness need longer time periods to reach the steadystate gaseous exchange. 52,53 Thus, the application of a 3-minute stage duration or less could not be enough to attain the steady-state gaseous exchange in specific populations.…”
Section: Time Interval For Data Selection and Analysismentioning
confidence: 99%
“…Indirect calorimetry is employed to determine EE because the heat released during the process of energy generation is directly proportional to the rate of oxygen uptake. Thus, measuring pulmonary gas exchange is a non‐invasive method to measure energy expended from processes that depend upon oxygen 41 …”
Section: Discussionmentioning
confidence: 99%
“…BJ-TF, however, are able to estimate kinetic feature values with multiple input transitions, e.g., for time-domain analyses of pseudo-random binary sequences of the cycling load [30], or during unsupervised physical activities. As physical activity and VO 2 can nowadays be measured with wearable devices [31,32], combining these measurements with BJ-TF modelling can produce frequent estimates of kinetic feature values during standard unsupervised training sessions, without the need for elaborate testing procedures. Similar models have already been successfully used to model heart rate responses during road cycling [33].…”
Section: Discussionmentioning
confidence: 99%